(untitled) - Jolicoeur, Thierry (Comptes Rendus. Physique, 2025)
The fractional quantum Hall effect (FQHE) realized in two-dimensional electron systems is explained by the emergent composite fermions (CF) out of ordinary electrons. It is possible to write down explicit wavefunctions explaining many if not all FQHE states. In bilayer systems there is a regime at integer filling of the lowest Landau level that displays a spontaneous breakdown of the U(1) relative phase between the two layers. This can be seen as interlayer phase coherence (ILC) in terms of electrons. Recent experiments in double layer samples of graphene have revealed the appearance of many FQHE states unique to the bilayer case. We discuss extensions of the CF idea in this situation as well as the possible existence of ILC of CFs.